Election, Atonement, and the Holy Spirit : Through and beyond Barth's Theological Interpretation of Scripture - Grebe, Matthias (Princeton theological monograph series, 2015)
Election, Atonement, and the Holy Spirit' is an examination of the doctrines of election and atonement in Karl Barth's 'Church Dogmatics', taking up Barth's own challenge to his reader to surpass his argument and offer a better typological interpretation of the cultic texts. Barth's radical re-working of Calvin's doctrine of election is one of the most important developments in twentieth-century theology. Christ synthesizes for Barth a particular dialectic: the binary structure of God's Yes of election and God's No of rejection. The book's central question - how can Jesus simultaneously be bot.